Quand les hommes parlent á leurs dieux et á leurs ancêtres: étude des textes de libation ewe en tant que genre poetique - Glover, Daniel Kwame (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Master of Arts in Comparative Literature.